Pengaruh Social Presence terhadap Kemampuan Problem Solving dalam Kelompok pada Mahasiswa Universitas X - Reghina Hasna Nabilah; Angesti Najwa Maritza Putri; Exa Ilham Illahi; Eva Laelatul Fitri; Whisnu Yudiana (Humanitas (Jurnal Psikologi), 2023)
This study aims to determine the effect of the social presence that arises from turning on or turning off the camera on video conference on group problem solving ability. This study uses an experimental method with the instruments used are the Social Presence Scale and the Tower of Hanoi puzzle by measuring reaction time, latency, and the number of movements of the respondent group (N=79). The results indicated that there are no significant differences in social presence, reaction time, latency, and the number of movements between the group that turned on the camera and the group that turned off the camera (p>0.1). This result could be caused by differences in the tendency to actively argue, individual domination, and differences in knowledge about the problem. The implication of this study will be discussed later in this article.